2021
DOI: 10.1063/5.0044177
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling exciton processes in Ir(ppy)3:CBP OLED films upon photoexcitation

Abstract: Emissive layers in phosphorescent organic light-emitting diodes commonly make use of guest-host blends such as Ir(ppy) 3 :CBP to achieve high external quantum efficiencies. However, while the Ir(ppy) 3 :CBP blend has been studied experimentally, crucial questions remain regarding how exciton diffusion is dependent on the distribution of the guest in the host, which can currently only be addressed at the atomic level via computational modeling. In this work, kinetic Monte Carlo simulations are utilized to gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…16 The KMC simulations were performed at 300 K, and for this reason, the morphologies were equilibrated at 300 K for at least 5 ns before the KMC simulations were initiated. The interaction parameters for CBP and the graphene substrate were identical to those used in previous work, 21 and the interaction parameters for Ir(ppy) 2 (acac) were taken from the work of Lee et al 16…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The KMC simulations were performed at 300 K, and for this reason, the morphologies were equilibrated at 300 K for at least 5 ns before the KMC simulations were initiated. The interaction parameters for CBP and the graphene substrate were identical to those used in previous work, 21 and the interaction parameters for Ir(ppy) 2 (acac) were taken from the work of Lee et al 16…”
Section: Methodsmentioning
confidence: 99%
“…The scheme used to generate the vacuum-deposited layers was identical to that described previously. 21,[23][24][25] A total of eight molecules were deposited every 14 ps until the total number of molecules matched that of the systems generated by the solution deposition MD simulations. Each molecule was selected at random to be either Ir(ppy) 2 (acac) or CBP in accordance with the target molar ratio (2:43, i.e., a guest concentration of 5 wt.…”
Section: B Vacuum Depositionmentioning
confidence: 99%
“…20 Subsequent studies utilized elements of the PyThinFilm package to perform vacuum deposition simulations of both OLED and OSC thin films. These include: (I) Lee et al 2017 44 who investigated the transition dipole distribution of OLED emitter molecules, (II) Lee et al 2018 30 who reported an analysis of the morphology of a low donor concentration OSC bulk heterojunction film, (III) Lee et al 2019 35 who described a comparison of smooth and rough substrate morphology on molecular orientation within a neat OSC film, (IV) Gao et al 2020 5 who demonstrated that the charge-transport and photophysical properties were directly related to morphological features observed at 5 different blend ratios within 34 nm × 34 nm OLED films comprising over 14 000 molecules, and finally, (V) Sanderson et al 2021 45 who showed that the host−guest blend morphologies could be used to investigate exciton transport in an OLED thin film using kinetic Monte Carlo simulations.…”
Section: ■ Applicationsmentioning
confidence: 99%
“…Clustering due to phase separation has also been shown in OLEDs at low concentrations (6 wt%). [ 22 ] To limit this phase segregation, polymers have been developed that contain photochromic moieties. To that end, side‐chain photochromic polymers have been developed by Kobatake [ 23 ] and Branda.…”
Section: Introductionmentioning
confidence: 99%